Morphology of the terminal abdominal segments in females of Triatominae (Insecta: Hemiptera: Reduviidae) - Santos Rodrigues, Juliana Mourao dos; Rosa, Joao Aristeu da [UNESP]; Figueiredo Moreira, Felipe Ferraz; Galvao, Cleber (Elsevier B.V., 2018)
Triatominae (Insecta: Hemiptera: Reduviidae) includes 151 extant species that are all potential vectors of Chagas disease. The relationships among these species have been recently studied based on molecular and cytogenetical approaches, and although the morphology of these insects is fairly described, wide comparative studies and cladistics analysis based on this feature are lacking. A comparative study of the terminal abdominal segments in females of 26 species of Triatominae was performed in order to evaluate their importance for the distinction of genera and species, and obtain characters to be used in cladistics analyses. The results showed that the short combined segments IX and X in dorsal view is not diagnostic for Rhodnius, and the elongated trapezoidal dorsal shape of combined segments IX and X is not exclusive of Panstrongylus. There are diagnostic features at the generic level for Rhodnius and Dipetalogaster, but not for the other genera studied. Among the structures examined, tergite IX is the most valuable for distinguishing species of Triatominae. The female terminalia is useful for the specific identification of Triatominae, but cannot be used to diagnose most genera or to directly assess supraspecific relationships. These can only be unveiled by using additional morphological and/or molecular data in broad cladistics analyses.
Keywords: Chagas disease; External morphology; Kissing bugs; Taxonomy